Transmission status of lymphatic filariasis in hotspots of filarial infection, persistent districts of nepal during post-MDA surveillance - Pramod Kumar Mehta; Mahendra Maharjan (PLoS ONE, 2026)
Background The lymphatic filariasis (LF) elimination program in Nepal was launched in 2003, three years after the implementation of a global program to eliminate lymphatic filariasis globally. Based on antigenic prevalence below the cut-off value, i.e., ≤ 2% shown by the transmission assessment survey (TASI) report of 2017–2018, the program was stopped in Nepal. The report indicated that antigen-positive children were clustered in the community and considered hotspots. In order to find the status of lymphatic filariasis transmission at the community level, the present study was designed in the hotspots to assess antigenemia among the children born after mass drug administration (MDA), along with vector infection/infectivity in identified hotspots of Central Nepal. Methods Each of two districts from the hilly and Terai regions of Central Nepal was selected based on comparatively high antigenic prevalence shown by previous TASI reports, and a descriptive cross-sectional study was designed. Two specific methods were employed: a Filarial Test Strip (Alere, Scorborough, ME) was used for antigenemia (n = 791) among children, and gravid traps were used for vector mosquito collection. Parous mosquitoes (n = 3344) were dissected for infection/or infectivity. Results The result indicated that antigen-positive cases were unexpectedly increased in hotspots of one each from the hilly region (Dhading) and Terai region (Mahottari), i.e., above the critical level (≥ 2%). Antigen prevalence increased from baseline prevalence, which was significantly associated with the number of MDA rounds but not with MDA coverage. The upper confidence limit of antigenemia and Mf infection was above the critical cut-off value in hotspots of all selected endemic districts. However, none of the vector mosquitoes, such as Culex quinquefasciatus, was found to be infected with any larval stage of filarial nematode. Conclusions The result showed an increase in antigenemia and Mf prevalence in high baseline prevalence areas with fewer MDA rounds. Lack of correlation between filarial infection in humans and xenomonitoring could be low sensitivity of xenomonitoring by microscopy. TAS-based assessment of antigenemia in children for stopping MDA can be supplemented with molecular xenomonitoring in hotspots.